Сказки в картинках - Сутеев Владимир Григорьевич (Библиотека начальной школы, 2015)
Экземпляры: ф.7 (20150921) / Инвентарный номер: 47069 / Цена: 88.00 / Сис.шифр: Д / Авт.знак: С 90 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6